Sanitation and life - Gilstrap, Effie (My University, 1892)
Introduction: Centuries ago, in a wilderness, Moses gave to the Jewish people laws, which us as Christians are only beginning to formulate. The pillar of fire and cloud was leading them over scorching deserts and through malicious valleys, beneath the burning oriental sun. Travelling and camping in companies of thousands, only the laws of sanitation preserved them from extermination by pestilence. Today the well-known healthfulness and longevity of the Jews, despite marvelous persecutions, are living proofs of the immutability of the laws of health and heredity. In Greece Gallus taught the truths of hygiene, while in the ruins of Roman baths, aqueducts, and even us have witnessed of the goal and sanitary knowledge of the ancients. The laws of this science to the world was marked by “pestilence that walketh in darkness, and destruction that wasteth at noon day. Only in the accidental purity of country life was the health of the nations for many years. Later the sciences of chemistry, botany, and medicine combined have shown the relations of sanitation to man, and the reform sought by the philanthropists of all ages.
Citation: Gilstrap, Effie. Sanitation and life. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Heredity; Health; Sensation; Herd immunity; Immunization; Animal Husbandry; Theses; Manuscripts (documents)